Transition Fault Coverage For Different Implementations Of The Circuit - Bareiša, E.; Jusas, V.; Motiejūnas, K.; Šeinauskas, R. (Elektronika ir Elektrotechnika, 2005)
The design complexity of systems on a chip drives the need to reuse legacy or intellectual property cores, whose gate-level implementation details are unavailable. The core test depends on manufacturing technologies and changes permanently during a design lifecycle. The purpose of this paper is to assist to designer in the decision making how to test transition faults of re-synthesized cores. We have performed various comprehensive experiments with combinational benchmark circuits. Our experiments show that the test sets generated for a particular circuit realization fail to detect in average only less than 1.5% of the transition faults of the re-synthesized circuit but in some cases this figure is more than 9%. The same trends are valid for stuck-at faults of different implementations, too. The double-detection test sets declined almost twice both the maximum and the average percent of undetected transition faults for all implementations of the circuits, except one singular implementation of one circuit. Ill.6, bibl. 17 (English, summaries in Lithuanian, English and Russian).